Deschampsia antarctica population dynamics given the trends in air temperature and penguin activity - Nataliia Miryuta; Denys Pishniak; Valentyna Malanchuk; Anton Puhovkin; Ivan Parnikoza (Ukrainian Antarctic Journal, 2025)
The main objective of the study is to describe the dynamics of the total size of Deschampsia antarctica population of Galindez Island, Argentine Islands, the maritime Antarctic, during 1964–2021, both in total and as eight sectoral groups of populations and eleven separate populations. The first task is to search for possible dependence of the dynamics of the total number of plants on the average monthly air temperature. Assessing the robustness of the Galindez population (G-population), sectoral groups of populations (sectoral populations), and individual populations (populations) by phase trajectories to relate them to the effects of meteorological and other variables is the next task. Methods for estimating the population size, the cover, and morphometric parameters (leaf length and flower length, respectively) of D. antarctica were used for the 2013/2014–2020/2021 and 2013/2014–2023/2024 seasons. Meteorological data from a long-term meteorological observations database were used. Topological analysis was used to determine population robustness. The dependence of the plants’ total number dynamics in the period 1964–2021 on the average monthly air temperature in September and February was shown. The dynamics of the sectoral populations and populations were compared with meteorological variables and other factors. The general dynamic of the G-population was described by a third-degree polynomial fit. At the same time, we managed to find a connection between the G-population and air temperature only in certain critical months of seasonal development – September and February. The individual sectors of the island exhibited significantly heterogeneous plant population trends, which may be attributed to environmental heterogeneity. The topological analysis allows to expand the populations’ classification under the external factors’ influence in the dynamics. Changing external conditions can lead to some populations’ transitioning from one robust state to another, or from an unrobust state to a robust one and vice versa. In particular, the penguin invasion over the past 3 years has destroyed the D4 population, whose state was described by a strange attractor over 8 seasons; the D6 population also influenced by penguins has transitioned from a stable torus state to a strange attractor state, the D10 population has transitioned from an unrobust torus state to a limit cycle state in the last three of the 11 years of research.